PERSEPSI MAHASISWA MAKASSAR TERHADAP PENERAPAN AKSARA HANGEUL DALAM BAHASA CIACIA - Muhammad Darwis; Lukman; Rahmatia (Universitas Hasanuddin, 2021)
This scientific paper discusses the perception of Makassar students on the application of Hangeul script in the Ciacia language. This study aims to try to explain the views of students from the Ciacia tribe who are studying in Makassar City. The results of the analysis show that Makassar students' perceptions of the application of Hangeul script in the Ciacia language are not uniform, but in general there are two opinions, namely the positive and negative. Negative perceptions came from students at the University of Muhammadiyah Makassar who viewed the application of Hangeul script in the Ciacia language as an unwise decision because it was considered to be detrimental to society, eliminating the identity of the Ciacia tribe, causing language interference, the forgotten language of the ancestors.